AI-Augmented Goal Programming: Addressing Complex Real-World Challenges in Applied Mathematics (International Journal of Scientific Research in Science and Technology, 2025)
In complex real-world environments characterized by conflicting objectives and dynamic constraints, conventional Goal Programming (GP) approaches often struggle to deliver flexible and adaptive solutions. This paper presents an AI-augmented Goal Programming framework that integrates artificial intelligence techniques—such as neural networks for demand prediction and evolutionary algorithms for multi-objective optimization—to enhance traditional GP models. The proposed approach allows real-time adjustment of priorities, constraints, and aspiration levels based on contextual data and system feedback. Case studies in healthcare logistics, renewable energy planning, and supply chain optimization demonstrate the framework’s efficacy in producing robust and high-quality solutions. Comparative numerical simulations show that the AI-enhanced GP model significantly outperforms classical GP in adaptability, accuracy, and computational efficiency. This research contributes to the fusion of intelligent systems and mathematical programming, providing a scalable decision-support methodology for addressing multifaceted challenges in applied mathematics.